Algorithm of Berthing and Maneuvering for Catamaran Unmanned Surface Vehicle Based on Ship Maneuverability - Gongxing Wu; Mingyuan Zhao; Yu Cong; ZhiWen Hu; Guofu Li (Journal of Marine Science and Engineering, 2021)
In the complex port environment, ship berthing manipulation is one of the most difficult operations. In this study, an algorithm of berthing and maneuvering was designed for a catamaran unmanned surface vehicle (USV), which is used for port patrol and protection. Considering the influence of wind, waves, and currents, the mathematical model of the maneuvering movement for the twin-hull and twin-propeller USV was established. Based on the Visual Studio development platform, the USV’s berthing manipulation simulation software was designed. Through the turning simulation experiment of the catamaran USV under different differential rotation speeds of the twin propellers, the relationship between the ship’s turning radius and the propeller speed difference was obtained. A simulation experiment of decelerating and stopping ships at different speeds was carried out, which can provide a reference for speed control when berthing. A berthing maneuvering algorithm based on ship maneuverability was proposed. USV’s berthing algorithm includes three stages: approach process, turning process, and berthing process. In the approach process, the appropriate approach speed was select according to the rotation angle. In the turning process, the right and left propeller speed differences were select. In the berthing process, the berthing speed was controlled according to the berthing distance. In the port environment, a berthing simulation experiment for catamaran USV was carried out. The simulation results show that based on the berthing and maneuvering algorithm, the efficiency and safety of catamaran USV berthing can be improved.